Evaluating the plasmon-exciton interaction in ZnO tetrapods coupled with gold nanostructures by nanoscale cathodoluminescence. (10th February 2021) - Villani, M; Rossi, F; Calestani, D; Salviati, G; Fabbri, F
Abstract: Plasmon-exciton coupling is gaining increasing interest for enhancing the performance of optoelectronic, photonic and photo-catalytic devices. Herein we evaluate the interaction of excitons in zinc oxide tetrapods with surface plasmons of gold nanostructures with different morphologies. The gold nanostructures are grown in situ on ZnO tetrapods by means of a photochemical process, resulting in clean interfaces. The modification of the synthesis parameters results in different morphologies, as isolated nanoparticles, nano-domes or nanoparticles aggregates. Plasmon-exciton interaction is evaluated by means of cathodoluminescence spectroscopy and mapping at the nanoscale. The ZnO excitonic emission is strongly blue-shifted and broadened in close proximity of the gold nanostructures. This effect is explained by the formation of a Schottky barrier that is strongly mediated by the morphology of metal nanostructures.